AUTONOMY OF KERINCI’S KUNUN TOWARD CHARACTER EDUCATION IN PRIMARY SCHOOLS IN SUNGAI PENUH CITY (OTONOMI KUNUN KERINCI TERHADAP PENDIDIKAN KARAKTER DI SEKOLAH DASAR DI KOTA SUNGAI PENUH) - Suci Maiza; Megi Vornika (Jurnal Gramatika, 2020)
This study is based on the phenomenon of oral literature development, especially prose development which underwent a quite serious stagnation in Sungai Penuh City. In schools, especially in primary schools, the introducing of prose was still in the form of a general scope, which was the same fable. Thus, it is important to improve the competency of beginner lecturers in the National Competitive Research to develop the utilization of folklore in the form of regional oral literature (Kunun) as a medium for implicating the value of character building in all primary school in Sungai Penuh City. The purpose of this study was to describe the structure, function, and the values of local wisdom and the autonomy of the application of Kunun as a media for improving the character building values in primary Schools in Sungai Penuh City. This study was a qualitative research with descriptive method. Data were collected through the study of literature, direct observation followed by documentation and interviewed with informants. The results of the recording were transcribed into Kerinci regional language and then to Indonesian. The results showed that there were many characters of value in Kunun that could be used as learning media. Besides, the application and the autonomy of Kunun have not been implicated optimally due to several problems. One of them was the lack of references or supporting books about Kunun